Rhizosphere 16S-ITS Metabarcoding Profiles in Banana Crops Are Affected by Nematodes, Cultivation, and Local Climatic Variations - Ciancio, Aurelio; Rosso, Laura Cristina; Lopez-Cepero, Javier; Colagiero, Mariantonietta (Frontiers in Microbiology, 2022)
Agriculture affects soil and root microbial communities. Detailed knowledge is, however, needed on the effects of cropping on rhizosphere, including biological control antagonists (BCA) of soil nematodes. A metabarcoding study was carried out on the microbiota associated to plant parasitic and other nematode functional groups present in banana farms in Tenerife (Canary Islands). Samples included rhizosphere soil from cv Pequeña Enana or Gruesa and controls collected from adjacent sites, with the same agroecological conditions without banana roots. To characterize bacterial communities, the variable V3 and V4 regions of the 16S rRNA ribosomal gene were amplified, whereas the ITS region was used for the fungi present in the same samples. Libraries were sequenced with an Illumina MiSeq™ in paired ends with 300-bp read length. For each sample, plant parasitic and other nematodes were extracted from soil, counted and identified. Phytoparasitic nematodes were mostly found in banana rhizosphere. They included Pratylenchus goodeyi, present in northern farms. Helicotylenchus spp. included H. multicinctus, found both in northern and southern farms. Metabarcoding data showed a direct effect of cropping on the microbial communities, and latitude-related factors, that separated northern and southern controls from banana rizosphere samples. Several fungal taxa known as nematode BCA were identified, with endophytes, mycorrhizal species, and obligate Rozellomycota endoparasites, almost only present in banana samples. Dominant bacterial phyla were Proteobacteria, Actinobacteria, Planctomycetes, Bacteroidetes, Chloroflexi and Acidobacteria. ITS data showed several OTUs belonging to Sordariomycetes, including biocontrol agents, such as Beauveria sp., Arthrobotrys spp., Pochonia chlamydosporia and Metarhizium anisopliae. Other taxa included Trichoderma harzianum, T. longibrachiatum, T. virens, and Fusarium spp., together with mycoparasites such as Acrostalagmus luteo-albus. However, only a Dactylella sp. a showed a correlation with predatory nematodes. Differences were found among the nematode guilds, as phytoparasitic, free living and predatory nematode groups were correlated with a specific subset of other bacteria and fungi. Crop cultivation method and soil texture showed differences in taxa representations when considering other farm and soil variables. Data showed changes in rhizosphere and soil microbiota related to trophic specialization and specific adaptations, affecting decomposers, beneficial endophytes, mycorrhizae or BCA, as well as plant pathogens.